Group Theoretic Study of Brenke Type Polynomials - Bajracharya, Shanti (Tribhuvan University Journal, 2010)
Not available.Key words: Brenke; PolynomialsTribhuvan University Journal Vol. XIX, No. 2, 1996 Page: 11-23  Uploaded Date: 29 October, 2010